Development of Waqf Forest in Indonesia: The SWOT-ANP Analysis of Bogor Waqf Forest Program by Bogor Waqf Forest Foundation - Khalifah Muhamad Ali; Salina Kassim (Jurnal Manajemen Hutan Tropika, 2021)
Some communities and governments in Indonesia have taken the initiative to develop waqf forests to solve forest conservation problems. However, research on waqf forest development is still rarely studied. This study aims to improve the strategy of waqf forest development in Indonesia. SWOT method is used to identify the strengths, weaknesses, opportunities, and threats and the possible development strategies of the Bogor Waqf Forest as a manager of Waqf Forest. The ANP method prioritizes these four aspects and the best strategy in developing the waqf forest. An aggressive strategy needs to be carried out by optimizing the existing legal organization and the well-educated human resources to inform the public about the waqf concept in Islam and its application in the waqf forest. Thus, the vast potential of cash waqf and waqif can be obtained. This paper is one of the pioneering articles that discuss waqf forest development strategies, especially in Indonesia. From this research, we recommend the Bogor Waqf Forest to resolve the legal aspects as an official waqf manager, and the government and Indonesian Ulema Council to issue regulation and fatwa regarding waqf forest.